Effects of increasing oregano oil on nursery pig performance - C R Neill; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 210 nursery pigs (PIC L327 × L42), with an initial weight of 11.9 lb and 21 d of age, were used in a 28-d growth study. The objective was to evaluate the effects of increasing oregano oil in diets for nursery pigs. Oregano oil is an extract derived from the Greek herb, Origanum vulgare, and has been speculated to have antimicrobial-like activity. Previous research at Kansas State University showed no improvement in growth performance in nursery pigs fed oregano oil (0.10% in the Phase 1 diet, and 0.05% in Phase 2). The present study evaluated growth performance of pigs fed diets containing either 0.05%, 0.10%, or 0.20% oregano oil for the entire 28-d study. There was no improvement in ADG, ADFI, F/G, or d-28 weights of pigs fed diets containing oregano oil, compared with performance of pigs fed the control diets. Also, there was no effect (P>0.15) of increasing the amount of oregano oil in the diet. But pigs fed neomycin-oxytetracycline had improved ADG, ADFI, and F/G (P<0.03), compared with those of pigs fed the control and oregano oil treatments, from d 0 to 14. Overall, (d 0 to 28), pigs fed neomycinoxytetracycline had better ADG and ADFI (P<0.006) than the pigs fed the control diet had, and better ADG, ADFI, F/G, and final body weight (P<0.04) than pigs fed the oregano oil treatment had.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Antibiotics; Nursery; Oregano oil; Pigs; Swine